2017
DOI: 10.1186/s40168-016-0222-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota dysbiosis contributes to the development of hypertension

Abstract: BackgroundRecently, the potential role of gut microbiome in metabolic diseases has been revealed, especially in cardiovascular diseases. Hypertension is one of the most prevalent cardiovascular diseases worldwide, yet whether gut microbiota dysbiosis participates in the development of hypertension remains largely unknown. To investigate this issue, we carried out comprehensive metagenomic and metabolomic analyses in a cohort of 41 healthy controls, 56 subjects with pre-hypertension, 99 individuals with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
1,203
13
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,276 publications
(1,385 citation statements)
references
References 66 publications
(92 reference statements)
76
1,203
13
21
Order By: Relevance
“…Hypertension is a major cardiovascular risk factor arising from a complex interplay of both genetic and environmental factors [90]. Germ-free mice that lack intestinal bacteria have relatively lower blood pressure when compared with conventional mice [91] and fecal transplantation from hypertensive human donors to germ-free mice elevates blood pressure in these animals [90], suggesting that the gut flora influences blood pressure.…”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is a major cardiovascular risk factor arising from a complex interplay of both genetic and environmental factors [90]. Germ-free mice that lack intestinal bacteria have relatively lower blood pressure when compared with conventional mice [91] and fecal transplantation from hypertensive human donors to germ-free mice elevates blood pressure in these animals [90], suggesting that the gut flora influences blood pressure.…”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 99%
“…Germ-free mice that lack intestinal bacteria have relatively lower blood pressure when compared with conventional mice [91] and fecal transplantation from hypertensive human donors to germ-free mice elevates blood pressure in these animals [90], suggesting that the gut flora influences blood pressure. In addition, rat studies and randomized clinical trials suggest that administration of probiotics can reduce blood pressure [92,93].…”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 99%
“…LPS is translocated to human circulation with chylomicrons and, therefore, increases after a meal, particularly in the case of a fatty meal, suggesting a prominent role of diet in modulating circulating LPS 9, 10. In addition, in some clinical settings such as hypertension, LPS may enter the systemic circulation as a consequence of increased gut permeability due to an impairment of tight junctions 11, 12. Experimental studies have showed that LPS is proatherogenic in vivo as its injection in mice and rabbits accelerates the formation of plaque 13.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is another major risk factor for the development of CVD. Experiments with germ-free mouse models have causally linked the gut microbiota and dysbiosis with the development of hypertension and vascular dysfunction [65,66]. In a study with 41 healthy controls, 56 pre-hypertensive subjects, and 99 individuals with primary hypertension, decreased microbial richness and diversity was revealed [66].…”
mentioning
confidence: 99%